Adaptation of the Growth Mindset Scale into Indonesian Language and Culture - Amelia, Najwa; Julaibib, Julaibib; Fikrie, Fikrie; Kusumaningrum, Vita Ariyanti (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study aims to adapt a growth mindset measurement tool into Indonesian language and culture and test its validity and reliability. The adaptation process followed the International Test Commission guidelines. Respondents were 310 people aged 18–25 years old spread across various regions of Indonesia. The results of Confirmatory Factor Analysis (CFA) showed a good fit of the measurement model (RMSEA = 0.062; CFI = 0.948; TLI = 0.928; SRMR = 0.040). Eight items in the scale were declared valid (Aiken's V > 0.72) and reliable with a McDonald's Omega value of 0.774. These findings indicate that the adapted measurement tool is suitable for measuring growth mindset in young adults in Indonesia. This instrument can be used in assessments, research, and psychological interventions aimed at increasing resilience and motivation in facing the challenges of early adult development.